The Molecular Mechanism of Sirt1 Signaling Pathway in Brain Injury of Newborn Rats Exposed to Hyperoxia - Kang, Lan; Dong, Wenbin; Ruan, Ying; Zhang, Rong; Wang, Xingyong (Biological & pharmaceutical bulletin, 2019)
The aim of the study was to investigate the changes in the reactive oxygen species (ROS), Sirt1, p53 and acetylated p53 in brain tissue of newborn rats exposed to hyperoxia to clarify the role of Sirt1 signaling pathway in brain injury. Neonate rats were randomly divided into normoxic group and hyperoxic group. Rats in the normoxic group were exposed to room air while the rats in the hyperoxic group were put in a hyperoxic chamber (80 ± 5% oxygen) for 1 to 14 d. Data, including weight growth, the water content of brain tissue, hematoxyline and eosin (H&E) and terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick-end labeling (Tunel) stain, ROS expression, the relative expression of Sirt1 mRNA and p53 mRNA, and the protein relative expression of Sirt1, p53 and acetylated p53 were analyzed at 1, 7 and 14 d after exposure. A reduced body weight and increased water content were observed in the brain tissue of hyperoxic group compared to normoxic group. HE staining and Tunel staining of brain tissue suggested that cell damaged after hyperoxic exposure. RT-PCR and Western blot results showed that the expression of Sirt1 in the hyperoxic group was lower than that in the normoxic group while the expression of p53 was higher than that in the normoxic group. In addition, Western blot data indicated acetylated p53 expression was higher in the hyperoxic group. Hyperoxic exposure can lead to brain injury in newborn Sprague-Dawley (SD) rats. These events might be regulated by the Sirt1 pathway, which downregulated the deacetylation of p53.